A longitudinal perspective on the differentiated valuation of formal education in Brazil in recent decades. Issue 1 (2nd January 2016) - Coradini, Odaci Luiz
Abstract : The central theme of this article is the relationship between formal education and earnings from a longitudinal perspective, taking into account indicators of social status. Variations in the respective trajectories, in different age cohorts, and in the comparison among different periods are discussed. The empirical material used is based on the microdata files of official statistics. The main techniques put into practice are those that are most focused on measuring the degree of interdependence among variables and those used for means comparison. Our general hypothesis is that the effects of schooling cannot be grasped in terms of education itself but instead in terms of its relationship to status in the social and power structures. One of this paper's principal observations is that of the general declining trend in the economic value of formal education, which varies depending on the level of education and social status. This devaluation is systematic and spans the entire studied universe; however, it focuses much more closely on those of lower social status, particularly for the groups with schooling that is either higher or lower than average.